The Position of Collateral Assets Owned by Third Parties in the Management and Administration of Bankruptcy Assets - Sitanggang, Rufina Astuti; Silalahi, Udin; Ginting, Jamin (Universitas Pelita Harapan, 2025)
Collateral serves as a guarantee for debt, with third parties often acting as guarantors or providing collateral that is not the debtor’s asset. When debtors file for bankruptcy, they may include third-party assets as collateral. The issue arises when these third-party assets are listed as bankruptcy assets, leading to conflicting court decisions—some include them as part of bankruptcy assets, while others do not. This dualism undermines legal certainty. The purpose of this research is to analyse the regulation regarding the position of collateral assets belonging to third parties in the management and administration of bankruptcy assets in Indonesia; the application of arrangements regarding collateral assets owned by third parties in the management and administration of bankruptcy assets in Indonesia; and legal certainty regulated over collateral assets belonging to third parties in bankruptcy in Indonesia. This research uses normative-juridical research with a statutory and conceptual approach with the analytical tools of agreement theory, legal certainty theory, and legal protection theory. Regulations regarding these issues are contained in Article 21 of Law Number 37 of 2004 and the guarantee agreement as an accessory agreement, Law Number 4 of 1996, Law Number 42 of 1999 and Book II and Book III of the Civil Code. The application of collateral payments owned by third parties in Indonesia's bankruptcy assets management and administration is currently has dualism. Pointing out that there are decisions that either declare collateral assets as bankruptcy assets or not, based on allegations and suspicions about ownership and the intention to accelerate the management and administration process. To address this, Article 21 of Law Number 37 of 2004 should be amended to clarify that bankruptcy assets are the assets of the bankrupt debtor and that collateral assets belonging to third parties are not included in bankruptcy assets as an affirmation of the previous provision.